Chromatin Conformation Links Putative Enhancers in Intracranial Aneurysm–Associated Regions to Potential Candidate Genes. Issue 9 (7th May 2019) - Laarman, Melanie D.; Geeven, Geert; Barnett, Phil; Rinkel, Gabriël J. E.; de Laat, Wouter; Ruigrok, Ynte M.; Bakkers, Jeroen
Abstract : Background: We previously showed that intracranial aneurysm (IA)–associated single‐nucleotide polymorphisms are enriched in promoters and putative enhancers identified in the human circle of Willis, on which IAs develop, suggesting a role for promoters and enhancers in IAs. We further investigated the role of putative enhancers in the pathogenesis of IA by identifying their potential target genes and validating their regulatory activity. Methods and Results: Using our previously published circle of Willis chromatin immunoprecipitation and sequencing data, we selected 34 putative enhancers in IA‐associated regions from genome‐wide association studies. We then used a chromatin conformation capture technique to prioritize target genes and found that 15 putative enhancers interact with the promoters of 6 target genes: SOX17, CDKN2B, MTAP, CNNM2, RPEL1, and GATA6 . Subsequently, we assessed the activity of these putative enhancers in vivo in zebrafish embryos and confirmed activity for 8 putative enhancers. Last, we found that all 6 target genes are expressed in the circle of Willis, on the basis of RNA sequencing data and in situ hybridization. Furthermore, in situ hybridization showed that these genes are expressed in multiple cell types in the circle of Willis. Conclusions: In 4 of 6 IA‐associated genome‐wide association study regions, we identified 8 putative enhancers that are active in vivo and interact with 6 nearby genes, suggesting that these genes are regulated by the identified putative enhancers. These genes, SOX17, CDKN2B, MTAP, CNNM2, RPEL1, and GATA6, are therefore potential candidate genes involved in IA pathogenesis and should be studied using animal models in the future.